Emerald handbook of evidence-informed practice in education : learning from international contexts. - Brown, Chris; Malin, Jowl R. (Emerlad Group Publishing, 2022)
Generating understanding into how to more routinely foster evidence-informed teaching practice globally, this ground-breaking handbook is vital reading for educational researchers, and especially those working close to practice, in all settings.